Introduction: Re-examining criminal process through the lens of integrity - Roberts, Paul; Hunter, Jill; Young, Simon N.M.; Dixon, David (Hart, 2016)
Criminal proceedings, it is often now said, ought to be conducted with integrity. But what, exactly, does it mean for criminal process to have, or to lack, 'integrity'? Is integrity in this sense merely an aspirational normative ideal, with possibly diffuse influence on conceptions of professional responsibility? Or is it also a juridical concept with robust institutional purchase and enforceable practical consequences in criminal litigation? The 16 new essays contained in this collection, written by prominent legal scholars and criminologists from Australia, Hong Kong, the UK and the USA, engage systematically with - and seek to generate further debate about - the theoretical and practical significance of 'integrity' at all stages of the criminal process. Reflecting the flexibility and scope of a putative 'integrity principle', the essays range widely over many of the most hotly contested issues in contemporary criminal justice theory, policy and practice, including: the ethics of police investigations, charging practice and discretionary enforcement; prosecutorial independence, policy and operational decision-making; plea bargaining; the perils of witness coaching and accomplice testimony; expert evidence; doctrines of admissibility and abuse of process; lay participation in criminal adjudication; the role of remorse in criminal trials; the ethics of appellate judgment writing; innocence projects; and state compensation for miscarriages of justice.